PENINGKATAN PERAN PEKARANGAN UNTUK MENDUKUNG PROGRAM PEKARANGAN PANGAN LESTARI (P2L) DI KOTA MADIUN - Ratna Mustika Wardhani; Wuryantoro; Djoko Setyo Martono (JURNAL DAYA-MAS, 2025)
If the yard is well maintained, it will provide an attractive, comfortable, healthy environment that makes us feel at home. We can utilize our yard according to our tastes and desires by planting productive plants such as ornamental plants, fruits, vegetables, spices, and medicines. Having your own business is one alternative solution that can be chosen. Homemakers who have an independent business outside of their main task of taking care of the family and utilizing their free time can also help their husbands fill the family's coffers. In addition, the yard can have an impact on education that can increase knowledge in the field of subjects, especially biology. Efforts to optimize the use and management of yards require the application of the concept of yard management as a sustainable urban agricultural area. Community service activities were carried out at six “KP2L”  locations in Madiun, using lecture methods and short training. The results of the activities showed an open view of the function of urban yards even though they were not supported by adequate land area. Introduction to soil-free cultivation techniques such as hydroponics, hydroponics, and aquaponics is very interesting to practice. Likewise, managing household organic waste into organic fertilizer is an interesting discourse that has great potential to be put into practice